Synthesis of Aminooxy Glycoside Derivatives of the Outer Core Domain of Pseudomonas aeruginosa Lipopolysaccharide - Si, Anshupriya; Sucheck, Steven J. (Frontiers in Molecular Biosciences, 2021)
Pseudomonas aeruginosa is a highly prevalent Gram-negative bacteria that is becoming more difficult to treat because of increasing antibiotic resistance. As chemotherapeutic treatment options diminish there is an increased need for vaccines. However, the creation of an effective P. aeruginosa vaccine has been elusive despite intensive efforts. Thus, new paradigms for vaccine antigens should be explored to developed effective vaccines. In these studies, we have focused on the synthesis of two L-rhamnose bearing epitopes common to glycoform I and II of the outer core domain of Pseudomonas aeruginosa lipopolysaccharide α-L-Rha-(1→6)-α-D-Glc-(1→4)-α-D-GalN-(Ala)-α-aminooxy (3) and α-L-Rha-(1→3)-β-D-Glc-(1→3)-α-D-GalN-(Ala)-α-aminooxy (4), respectively. The target trisaccharides were both prepared starting from a suitably protected galactosamine glycosides followed by successive deprotection and glycosylation with suitably protected D-glucose and L-rhamnose thioglycosides. Global deprotection resulted in the formation of targets 3 and 4 in 22% and 35% yield each. Care was required to modify basic reaction conditions to avoid early deprotection of the N-oxysuccinamido group. In summary, trisaccharides of the related to the L-rhamnose bearing epitopes common to glycoform I and II of the outer core domain of Pseudomonas aeruginosa lipopolysaccharide have been prepared as their aminooxy glycosides. The latter are expected to be useful in chemoselective oxime-based bioconjugation reactions to form Pseudomonas aeruginosa vaccines.